The Design of Mini Boiler Using Liquefied Petroleum Gas (LPG) for Tofu Home Industry - Susilawati,; Sahara, Siti (International Journal of Psychosocial Rehabilitation, 2020)
The tofu home industry in Subang Regency still uses traditional stove with firewood for boiling process. The obstacle which is experienced by the tofu entrepreneurs is the smoke produced from burning firewood can affect the sense of tofu and the smell becomes smell. The purpose of this study is to produce a mini boiler for the tofu home industry so that it can improve the quality of tofu. The research method consists of several stages, namely the process of design, making work preparation, preparation of the tools and materials needed, manufacturing process and assembly of mini boiler components and performance test The result of the study was created a mini boiler with dimensions outside the body diameter of a mini boiler 32.6 cm, length 80 cm, thickness 4 mm, steam tube diameter 22 cm, length 30 cm and thickness 4 mm, capacity 31.8 liters, the amount of heat generated at burner 41305,567 KJ/hour and heat propagation 2.339928 x 10-2 Cal/s on the burner and 0.66857665 x 10-2 Cal/s on the economizer, the amount of fuel needed is 12.7972 kg/hour. After using mini boiler, the quality of tofu is better and does not smell smoke, and is more hygienic because there is no black smoke from the boiling process.